Research of the economic potential of the enterprise - Shein, E. S.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It has been proved that the competitiveness of enterprises depends on many conditions, including methodological support for the formation of the strategic potential of an enterprise, necessary for its successful functioning in a competitive environment, on the state of legislation, in particular tax and antimonopoly, etc., and, first of all, the competitiveness of an enterprise is determined by its potential.
Дослідження економічного потенціалу підприємства
Keywords: economics; management; potential; factors; efficiency; production; market